2019
DOI: 10.1136/vr.105062
|View full text |Cite
|
Sign up to set email alerts
|

Little association between birth weight and health of preweaned dairy calves

Abstract: Intrauterine growth retardation (IUGR) may result in reduced birthweight and detrimental physiological alterations in neonates. This prospective cohort study was designed to assess if there exists an association between birthweight of dairy calves and incidence of bovine respiratory disease (BRD), neonatal calf diarrhoea (NCD) or mortality during the pre-weaning period. Calves (n=476) on 3 farms in South West England were weighed at birth. Farmers kept records of treatments for NCD and BRD and calves were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…As our sample was only from calves 9 d of age or less, older calves may reflect additional time at risk to develop clinical signs of disease. Weight was not found to be associated with health; a recent study in the United Kingdom similarly found no association between birth weight and calf health (Glover et al, 2019). Weight of calves in our study likely reflects both birth weight and early life nutrition.…”
Section: Discussioncontrasting
confidence: 79%
“…As our sample was only from calves 9 d of age or less, older calves may reflect additional time at risk to develop clinical signs of disease. Weight was not found to be associated with health; a recent study in the United Kingdom similarly found no association between birth weight and calf health (Glover et al, 2019). Weight of calves in our study likely reflects both birth weight and early life nutrition.…”
Section: Discussioncontrasting
confidence: 79%
“…For the study, the animals were distributed into two groups, according to the birth weight criterion, since this is an important parameter that can infer on the rate of dystocia, disease incidence, and lower performance of calves in dairy farms, although its may vary between farms (Holland and Odde, 1992;Jacobsen et al, 2000;Glover et al, 2019). Given this, at birth, all calves were weighed using a tape measure for medium-sized animals, obtaining an average weight of 35.45 ± 4.6 kg, and a median weight of 35.50 Kg.…”
Section: Methodsmentioning
confidence: 99%
“…Although other studies investigate the in uence of birth weight on calf performance (Glover et al, 2019), there are still few studies that correlate this parameter with the performance and metabolic pro le of neonates from IVF. In this sense, the aim of this study was to determine the in uence of birth weight on the metabolic, zootechnical, and health pro le of Girolando calves from IVF.…”
Section: Introductionmentioning
confidence: 99%
“…McCorquodale et al [ 211 ] reported higher mortality rates in LBW dairy calves. Other studies did not, however, find that LBW was a significant risk factor for either diarrhoea or BRD in dairy heifer calves [ 212 , 213 ].…”
Section: Follow-up Studies Investigating Fetal Programming and Fertilitymentioning
confidence: 99%